Parental Responsibility, Blameworthiness, and Bullying: Parenting Style and Adolescents' Experiences With Traditional Bullying and Cyberbullying. (June 2021) - Broll, Ryan; Reynolds, Dylan
Parents are deemed morally—and, increasingly, legally—responsible for their children's misbehavior, and their parental aptitude is questioned if their children are victimized. Parental responsibility laws and blameworthiness extend to common occurrences like bullying. Literature broadly supports these principles for some offenses through findings that effective parenting styles are associated with improved adolescent outcomes, but evidence about the relationship between parenting styles and bullying is underdeveloped and inconclusive. To study the relationship between parenting styles and traditional bullying and cyberbullying offending and victimization, data were collected from a sample of 435 Canadian middle and high school students. The results suggest that parenting styles are not associated with traditional bullying offending or victimization; however, neglectful parenting was associated with cyberbullying offending and indulgent parenting was associated with cyberbullying victimization. These findings suggest that the demandingness dimension of parenting, which is characterized by rule setting and monitoring, is important for cyberbullying prevention.